Country Economic Memorandum for Sao Tome and Principe - Background Note 12 : What is the Potential and Obstacles for the Fisheries Sector in São Tomé and Príncipe? - Serkovic, Mirko (World Bank, Washington, DC, 2019)
The purpose of this note is to give an overview of the fisheries sector in STP, its potential and obstacles, as well some policy recommendations to address these obstacles, ensure sustainable management of these resources and tap into its potential. It is organized in four section, besides this introduction. The second section describes the fishing sector in STP, while the third and the fourth outline the obstacles for the development of the artisanal and industrial fisheries respectively. The last section offers policy recommendations. Fisheries play an important role for the economic and social development of the country, however resources are likely over-exploited. Coastal marine resources are showing signs of full or overexploitation around the Sao Tome island. Before looking at increasing production of coastal resources, knowledge on the status of the fish stock would have to be improved through data collection and research to understand the potential of these resources and adequate sustainable management of these resources would have to be ensure through reinforced legal framework, governance and enforcement, as well as the potential development of co-management1 system between the STP authorities and the fishing communities.